2021
DOI: 10.1021/acs.orglett.1c02062
|View full text |Cite
|
Sign up to set email alerts
|

Annulative π-Extension (APEX) of Indoles to Pyrido[1,2-a]indoles Using 4-Oxo Peroxides as C4 Units

Abstract: Annulative π-extension (APEX) of 3-substituted indoles to pyrido[1,2-a]indoles is developed by using 4-oxo peroxides as π-extending reagents, which are employed as versatile C4 building blocks. This transformation is initiated by Brønsted acid-mediated Hock rearrangement of the peroxyl group. Notably, the pyrido[1,2-a]indole products are obtained by elimination of the indole moiety from the corresponding dihydropyrido[1,2a]indoles, which could be selectively formed at room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 50 publications
0
25
0
Order By: Relevance
“…Isolated by flash column chromatography (eluent: ethyl acetate/petroleum ether = 1:10, R f = 0.3) (69 mg, 79%). Color: yellow; 1 H NMR (600 MHz, CDCl 3 ) δ 8.05 (d,J = 8.3 Hz,1H), 7.77 (t, J = 7.3 Hz, 1H), 7.71 (t, J = 8.1 Hz, 2H), 7.65 (d,J = 7.3 Hz,2H), 7.55 (t, J = 8.1 Hz, 1H), 7.16 (t, J = 8.2 Hz, 1H), 6.88 (s, 1H), 6.72 (d, J = 8.6 Hz, 1H); 13 C{ 1 H} NMR (150 MHz, CDCl 3 ) δ 146. 3,145.8,145.7,133.5 (t,J = 24.3 Hz),132.1,131.6,129.7,129.1,128.5,127.4,123.3,121.1,115.1,112.1,108.5 3,3,3,3,3, -prop-1-yn-1-yl)-1-(p-tolyl)benzo [4,5]imidazo[1,2-a]pyridine-4-carbonitrile 3c.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 3 more Smart Citations
“…Isolated by flash column chromatography (eluent: ethyl acetate/petroleum ether = 1:10, R f = 0.3) (69 mg, 79%). Color: yellow; 1 H NMR (600 MHz, CDCl 3 ) δ 8.05 (d,J = 8.3 Hz,1H), 7.77 (t, J = 7.3 Hz, 1H), 7.71 (t, J = 8.1 Hz, 2H), 7.65 (d,J = 7.3 Hz,2H), 7.55 (t, J = 8.1 Hz, 1H), 7.16 (t, J = 8.2 Hz, 1H), 6.88 (s, 1H), 6.72 (d, J = 8.6 Hz, 1H); 13 C{ 1 H} NMR (150 MHz, CDCl 3 ) δ 146. 3,145.8,145.7,133.5 (t,J = 24.3 Hz),132.1,131.6,129.7,129.1,128.5,127.4,123.3,121.1,115.1,112.1,108.5 3,3,3,3,3, -prop-1-yn-1-yl)-1-(p-tolyl)benzo [4,5]imidazo[1,2-a]pyridine-4-carbonitrile 3c.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Color: yellow; 1 H NMR (600 MHz, CDCl 3 ) δ 7.95 (d,J = 8.3 Hz,1H),7.75 (dd,J = 8.5 Hz,5.1 Hz, 2H), 7.55 (t, J = 7.8 Hz, 1H), 7.43 (t, J = 8.5 Hz, 2H), 7.21 (t, J = 7.6 Hz, 1H), 6.85 (s, 1H), 6.76 (d, J = 8.7 Hz, 1H); 13 C{ 1 H} NMR (150 MHz, CDCl 3 ) δ 165. 4, 163.7, 146.1, 145.5, 144.8, 133.4 (t, J = 24.8 Hz), 131.0 (d, J = 8.5 Hz), 128.9, 128.1 (d,J = 3.4 Hz),127.5,123.5,121.0,117.2,117.1,114.9,112.0,108.7 (t, J = 7.0 Hz), 101.3; 19 F NMR (564 MHz, CDCl 3 ) δ −79.8 (t, J = 11.3 Hz, 3F), −106.9 (s, 1F), −110.3 (q, J = 11.3 Hz, 2F), −124.8 (s, 2F); HRMS (ESI) calcd for C 21 H 10 F 8 N 3 + [M + H + ] 456.0741, found 456.0735. 1-(4-Chlorophenyl)-3-(3,3,3,3,3,3,3-heptafluoro-3λ 8 -prop-1-yn-1-yl)benzo [4,5]imidazo[1,2-a]pyridine-4-carbonitrile 3f.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Later, we successfully applied the α-keto radical B produced by the oxidation of ketone to achieve 4-oxo peroxides (Scheme b) . Significantly, we demonstrated that both the 3-oxo and 4-oxo peroxides are versatile intermediates in organic synthesis . Inspired by these attractive results and based on the knowledge portfolio of the ring opening of cyclopropanols, we rationalized that 5-oxo peroxides could be achieved under the circumstance in which cyclopropanol serves as the β-keto radical C and applied in the iron-catalyzed radical relay reaction with alkenes and TBHP (Scheme c).…”
mentioning
confidence: 98%